A Rare Case of Late-onset Hemochromatosis Due to H63D Syndrome, a Diagnostic Challenge - N. M. M. Risly; I. K. Jayasinghe; N. Athauda; T. Eranga; J. F. Sahana (Sri Lanka Journal of Medicine)
H63D Syndrome (linked to a rarer H63D mutation in the HFE gene than the commoner C282Y mutation) despite causing mild iron overload can lead to significant morbidity than typical hemochromatosis. A 60-year-old, presented with Bell’s palsy, on further enquiry, had generalized pruritus, constipation, and neuropsychiatric involvement. Also, examination showed mild jaundice, cogwheel rigidity, and hyperpigmented face. Investigations revealed features of Child B cirrhosis with high transferrin saturation (TSAT) and hyperferritinemia with ultrasound confirmation. Genetics revealed a homozygous H63D mutation. He was treated with ferritin, TSAT, haemoglobin-guided venesections and iron chelation therapy (by deferasirox) with symptomatic management. He significantly improved clinically and biochemically highlighting the need for genetic testing when diagnosing hemochromatosis and ensuring biochemically guided treatment.